Agents of influence : Britain's secret intelligence war against the IRA / Aaron Edwards. - Edwards, Aaron (Merrion Press, 2021)
Recruited by British Intelligence to infiltrate the IRA and Sinn Féin during the height of the Northern Ireland Troubles, they were agents of influence. These spies played a pivotal role in the fight against the IRA. Now, for the first time, some of these agents have emerged from the shadows to tell their compelling stories. 'Agents of Influence' takes you behind the scenes of the secret intelligence war which helped bring the IRA's armed struggle to an end.